GCMS CHARACTERIZATION AND MOSQUITO REPELLING POTENTIAL EVALUATION OF COIL PRODUCED USING OCIMUM BACILLICUM OIL - Haruna, M. S.; Baba, Hauwa Gabi; Sani, Saadatu S. (FUDMA JOURNAL OF SCIENCES, 2023)
Mosquito a vector for many protozoa, bacterial and viral diseases facilitating their transmission to human, resulting to loss of millions of lives annually.  Its vectors capacity is enhanced by development of its resistance to many insecticides. The present study aimed at characterizing using FTIR and GC-MS methods of essential oil from Ocimum basilicum, production of mosquito repellent coil from the oil and bio-efficacy evaluation of the coil on adult mosquito (A. stephensis). The FTIR Spectral revealed the presences of P-OH, N-O, C-O, NO2, C=O, O-H, =C-H, O-H and C-X which correlate with the functional groups of the major phyto-chemical constituent compounds revealed by GC-MS spectral. 15 phyto-constituents were identified with 9, 12, 15-Octadecanoic acid as the major phyto-constituent with percentage of 35.61%. Bio-efficacy evaluation shows high potential of the coil at all concentration and with highest value at 300mg and 400mg compared to the result obtained for commercially made coil (Baygon) at laboratory condition. Ocimum basilicum can therefore be used as an alternative repellent ingredient to repel adult mosquito